2011
DOI: 10.1586/erp.11.42
|View full text |Cite
|
Sign up to set email alerts
|

Influence of demand-side measures to enhance renin–angiotensin prescribing efficiency in Europe: implications for the future

Abstract: Multiple and intensive demand-side measures enhanced prescribing efficiency. The more intense follow-up of ARB prescribing restrictions in Croatia had a greater influence on subsequent utilization patterns than Austria. Both findings confirm earlier studies. Reforms also favorably enhanced the prescribing of generic losartan once available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
221
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(239 citation statements)
references
References 33 publications
16
221
0
Order By: Relevance
“…Not surprisingly, there was convergence in utilization rates between the databases once the reimbursement restrictions were lifted for the statins (Tables 1 and 2) in view of the prevalence of CHD in Lithuania [15]. The lack of any major difference in the utilization of the renin-angiotensin inhibitors between the different databases with no prescribing restrictions in Lithuania (Tables 1 and 4), and similar utilization patterns to Western European countries in 2007 [10,26], further demonstrates that prescribing restrictions can appreciably influence subsequent utilization rates [21,28] and, as a result, demonstrating the need to accurately document ongoing reforms in any CNC study. The increase in statin utilization following the removal of prescribing restrictions (Table 3) further supports this.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Not surprisingly, there was convergence in utilization rates between the databases once the reimbursement restrictions were lifted for the statins (Tables 1 and 2) in view of the prevalence of CHD in Lithuania [15]. The lack of any major difference in the utilization of the renin-angiotensin inhibitors between the different databases with no prescribing restrictions in Lithuania (Tables 1 and 4), and similar utilization patterns to Western European countries in 2007 [10,26], further demonstrates that prescribing restrictions can appreciably influence subsequent utilization rates [21,28] and, as a result, demonstrating the need to accurately document ongoing reforms in any CNC study. The increase in statin utilization following the removal of prescribing restrictions (Table 3) further supports this.…”
Section: Discussionmentioning
confidence: 91%
“…Patented statins were restricted to second line in Norway and Finland, limiting their utilization in Finland to just 18.3% of total statin utilization, ARBs were restricted to second line after angiotensin converting enzyme inhibitors (ACEIs) in a number of European countries limiting their utilization, and more recently patented ARBs were restricted to second line versus generic ARBs in Austria and Belgium following generic availability again significantly reducing their use [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, these measures help fund increased drug volumes and new drugs without having to raise taxes or health insurance premiums. However, recent research has shown that among the proton pump inhibitors (PPIs), 3-hydroxy-3-methil-gluteryl-CoA reductase inhibitors (statins) and renin-angiotensin products, there is considerable variation in the prescribing of generics within a class or related classes once generics become available in a class [5,8,15,26,27]. Consequently, there are appreciable opportunities for countries to further enhance their prescribing of generics and lower their prescribing costs through learning from each other.…”
Section: Deman D-side Measur Es To En H An Ce Th E Pr Escr Ibin G Of mentioning
confidence: 99%
“…The plain ARBs compose 11.9% and ARB combinations make up 3.3% of all CV drugs DDD/TID. An increase in the use of ARB is also noticed in other countries despite prescribing restrictions by the authorities (29).…”
Section: Discussionmentioning
confidence: 94%